THERMAL SMEARING OF INFRARED PATTERN ON THE SURFACE OF A THIN FILM HTSC BOLOMETER - Gordiyenko, E. Yu.; Glushchuk, N. I.; Turutanov, O. G.; Fomenko, Yu. V.; Shustakova, G. V. (Видавничий дім «Академперіодика», 2019)
PACS numbers: 85.25.Pb,44.10.+jPurpose: Composite superconducting bolometers of various cooling levels are widely used in astronomy for detecting radiation in the far IR, submillimeter and millimeter wavelength ranges. The inter-element thermal crosstalk is one of the basic issues in the development of composite HTSC bolometer arrays. The smearing of the temperature pattern formed on the surface of an HTSC thin film/substrate structure by incident IR radiation is studied. The purpose of the work is to measure the spatial and temporal parameters of thermal smearing of an IR image on the film surface.Design/methodology/approach: The study exploits the method of scanning laser probe. The previously proposed approach to detect the spatial distribution of the intensity of external radiation using additional local thermal affect was also used. A laser beam focused on the surface heats a film area and brings it from superconducting to resistive state sensitive to external radiation. Scanning the entire structure with the laser probe is equivalent to moving the sensitive area thus providing the readout of the temperature pattern created by external radiation.Findings: The temperature relief is smeared due to thermal diffusion along the surface of an HTSC structure, which absorbs radiation. Thus, for a structure composed of YBa2Cu3O7-x thin film with the thickness of 200 nm on a 500 μm thick SrTiO3 substrate, the steady-state size of the thermal image is almost twice as large as the initial size of the IR image focused on the surface. The experimental data are consistent with the results of mathematical modeling of thermal processes during radiation absorption in the system. The thermal diffusion length and the characteristic time to achieve maximum heating of the film surface are studied as a function of the substrate thickness and the polling rate.Conclusions: Thermal smearing of IR images along the surface of composite HTSC bolometers imposes limitations on their spatial resolution, speed, and other parameters. Reducing such smearing can be achieved by decreasing the polling time and optimizing the thermal design of the film/substrate system. Since it is the thermal diffusion length, which determines the size of sensitive elements and the optimal spacing between them, the results can be used for designing the composite HTSC bolometer arrays.Key words: HTSC bolometer, IR pattern, thermal diffusion, laser probeManuscript submitted 18.04.2019 Radio phys. radio astron. 2019, 24(2): 136-143 REFERENCES1. GOSSORG, J., 1988. Infrared thermography. Fundamentals, Technique, Application. Moscow, Russia: Mir Publ. (in Russian).2. POSADA, C. M., ADE, P. A. R., AHMED, Z., ANDERSON, A. J., AUSTERMANN, J. E., AVVA, J. S., BASU THAKUR, R., BENDER, A. N., BENSON, B. A., CARLSTROM, J. E., CARTER, F. W., CECIL, T., CHANG, C. L., CLICHE, J. F., CUKIERMAN, A., DENISON, E. V., DE HAAN, T., DING, J., DIVAN, R., DOBBS, M. A., DUTCHER, D., EVERETT, W., FOSTER, A., GANNON, R. N., GILBERT, A., GROH, J. C., HALVERSON, N. W., HARKEHOSEMANN, A. H., HARRINGTON, N. L., HENNING, J. W., HILTON, G. C., HOLZAPFEL, W. L., HUANG, N., IRWIN, K. D., JEONG, O. B., JONAS, M., KHAIRE, T., KOFMAN, A. M., KORMAN, M., KUBIK, D., KUHLMANN, S., KUO, C. L., LEE, A. T., LOWITZ , A. E., MEYER, S. S., MICHALIK, D., MILLER, C. S., MONTGOMERY, J., NADOLSKI, A., NATOLI, T., NGUYEN, H., NOBLE, G. I., NOVOSAD, V., PADIN, S., PAN, Z., PEARSON, J., RAHLIN, A., RUHL, J. E., SAUNDERS, L. J., SAYRE, J. T., SHIRLEY, I., SHIROKOFF, E., SMECHER, G., SOBRIN, J. A., STAN, L., STARK, A. A., STORY, K. T.,  SUZUKI, A., TANG, Q. Y., THOMPSON, K. L., TUCKER, C., VALE, L. R., VANDERLINDE, K., VIEIRA, J. D., WANG, G., WHITEHORN, N., YEFREMENKO, V., YOON, K. W. and YOUNG, M. R., 2018. Fabrication of Detector Arrays for the SPT-3G Receiver. J. Low Temp. Phys. vol. 193, is. 5-6, pp. 703–711. DOI: https://doi.org/10.1007/s10909-018-1924-13. DELERUE, J., GAUGUE, A., TESTE, P., CARISTAN, E., KLISNICK, G., REGON, M. and KREISLER, A., 2003. YBCO mid-infrared bolometer arrays. IEEE Trans. Appl. Supercond. vol. 13, is. 2, pp. 176–179. DOI: https://doi.org/10.1109/TASC.2003.8136744. BEHNER, H., RÜHRNSCHOPF, K., WEDLER, G. and RAUCH, W., 1993. Surface reactions and long time stability of YBCO thin films. Physica C. vol. 208, is. 3-4, pp. 419–424. DOI:  DOI : https://doi.org/10.1016/0921-4534(93)90216-D5. COPETTI, C. A., SCHUBERT, J., ZANDER, W., SOLTNER, H., POPPE, U. and BUCHAL, CH., 1993. Aging of superconducting YBa2Cu3O7-x structures on silicon. J. Appl. Phys. vol. 73, is. 3, pp. 1339–1342. DOI: https://doi.org/10.1063/1.3532526. KHREBTOV, I. A., 2002. Noise properties of high temperature superconducting bolometers. Fluct. Noise Lett. vol. 2, no. 2, pp. R51–R70. DOI: https://doi.org/10.1142/S02194775020006717. VERGHESE, S., RICHARDS, P. L., CHAR, K., FORK, D. K. and GEBALLE, T. H., 1992. Feasibility of infrared imaging  ging arrays  arrays using  using high  high T T c c superconducting bolometers. J. Appl. Phys. vol. 71, is. 6, pp. 2491–2498. DOI: https://doi.org/10.1063/1.3510638. KREISLER, A. J. and GAUGUE, A., 2000. Recent progress in high-temperature superconductor bolometric detectors: from the mid-infrared to the far-infrared (THz) range. Supercond. Sci. Technol. vol. 13, is. 8, pp. 1235–1245. DOI: https://doi.org/10.1088/0953-2048/13/8/3219. GORDIYENKO, E. YU., SLIPCHENKO, N. I. and GARBUZ, A. S., 2002. High temperature superconducting microthermometers for multi-elements IR radiation detectors. Radioelectronika i informatika. no. 3, pp. 38–41. (in Russian). Available from: https://cyberleninka.ru/article/n/vysokotemperaturnye-sverhprovodnikovye-mikrotermo-metry-dlya-mnogoelementnyh-priemnikov-ik-izlucheniya10. ZHURAVEL, A. P., SIVAKOV, A. G., TURUTANOV, O. G., OMELYANCHOUK, A. N., ANLAGE, S. M., LUKASHENKO, A., USTINOV, A. V. and ABRAIMOV, D., 2006. Laser scanning microscopy of HTS films and devices (Review Article). Low Temp. Phys., vol. 32, no. 6, pp. 592–607. DOI: https://doi.org/10.1063/1.221537611. FARDMANESH, M., ROTHWARF, A. and SCOLES, K. J., 1995. YBa2Cu3O7-x infrared bolometers: Temperature dependent responsivity and deviations from the dR/dT curve. J. Appl. Phys. vol. 77, is. 9, pp. 4568–4575. DOI: https://doi.org/10.1063/1.35942012. ZHURAVEL, A. P., USTINOV, A. V., ABRAIMOV, D. and ANLAGE, S. M., 2003. Imaging local sources of inter-modulation in superconducting microwave devices. IEEE Trans. Appl. Supercond. vol. 13, is. 2, pp. 340–343. DOI: https://doi.org/10.1109/TASC.2003.81373113. YEFREMENKO, V., GORDIYENKO, E., PISHKO, V., PISHKO, O. and NOVOSAD, V., 2007. Method for detection and imaging over a broad spectral range. US Patent No. 7,274,019 B2.14. YEFREMENKO, V., GORDIYENKO, E., SHUSTAKOVA, G., BADER, S. D. and NOVOSAD, V., 2005. Superconducting microbolometer with controllable coordinate sensitivity: an alternative approach to FPA design. In: B. F. ANDRESEN and G. F. FULOP, eds. Proceedings of SPIE. Infrared Technology and Application XXXI. vol. 5783,pp. 967–973. DOI: https://doi.org/10.1117/12.60364715. GORDIYENKO, E., SHUSTAKOVA, G., FOMENKO, YU. V. and GLUSHCHUK, N. I., 2013. Thermal Imaging System Based on a High Temperature Superconductor. Instrum. Exp. Tech. vol. 56, is. 4. pp. 485–490. DOI: https://doi.org/10.1134/S0020441213030196